The quality of robusta coffee (Coffea canephora) with the addition of Leuconostoc mesenteroides during wet fermentation - FERA ROSALIANA; YULIANA RENI SWASTI; EKAWATI PURWIJANTININGSIH (Biodiversitas Journal of Biological Diversity, 2025)
Abstract. Rosaliana F, Swasti YR, Purwijantiningsih E. 2025. The quality of Robusta coffee (Coffea canephora) with the addition of Leuconostoc mesenteroides during wet fermentation. Biodiversitas 26: 3334-3342. Coffee consumption is inseparable from the health benefits of antioxidants in coffee beans. However, coffee contains caffeine, which affects the nervous system, kidneys, and blood vessels. Caffeine content is usually reduced using organic solvents and physical treatment. However, caffeine reduction using microorganisms, such as Lactic Acid Bacteria (LAB), is underexplored. This research aimed to improve the quality of robusta coffee by increasing its antioxidant activity and reducing caffeine content by adding Leuconostoc mesenteroides during wet fermentation. L. mesenteroides is a proteolytic bacterium that can degrade caffeine in coffee beans and enhance antioxidant activity. Robusta coffee has a higher caffeine content than Arabica. Therefore, the caffeine content needs to be reduced. The caffeine content was analysed using the HPLC method, and antioxidant activity was conducted using the DPPH method. The experimental design in this study was a completely randomized factorial design with two factors: fermentation time and the addition of L. mesenteroides. Each treatment has 3 replications. The data were analyzed using Analysis of Variance (ANOVA). The results show that the average caffeine content of espresso robusta green coffee beans was 1.26-2.19 mg/mL, while that of roasted coffee beans was 2.05-3.04%. Adding L. mesenteroides reduces the caffeine content of coffee beans by 13.34%. Espresso with green coffee beans has the average antioxidant activity ranging from 17.57±0.08%-23.32±0.08%, and espresso with roasted coffee beans ranges from 80.97±0.21%-84.87±0.08%; L. mesenteroides increases the antioxidant activity by 1.06%. In addition, the average moisture content of robusta green coffee beans fermented at 6, 12, and 18 hours with natural microbes and the addition of L. mesenteroides reached a moisture content of 9.82±0.10%-10.83±0.32%, while the roasted coffee beans ranged from 3.33±0.23%-3.80±0.16%. The average protein content of green coffee beans ranged from 10.51±0.76% to 13.28±0.67%, and roasted coffee beans from 11.38±0.88% to 12.55±0.50%. The total phenolic compound of green coffee beans ranged from 18.14±0.31 to 31.32±0.14 mg GAE/g, while the roasted beans reached 85.37±0.30 to 123.87±1.01 mg GAE/g. Adding L. mesenteroides reduces pH of green and roasted coffee beans. Testing other LABs on coffee beans can further explore these potential health benefits.